1
$\begingroup$

I'm trying to solve the following system of equations:

$$l_1 \sin(\alpha) = l_2 \cos(\gamma) + l_3 \sin(\beta)$$

$$l_2 \sin(\gamma) + l_1 \cos(\alpha)=l_3 \cos(\beta) + l_4$$

with the unknowns $\beta, \gamma \in \Bbb R⁺$, the constants $l_1$, ..., $l_4$ $\in$ $\Bbb R⁺$ and the(known) variable $\alpha \in [0,\pi]$.

What I need is a function $\beta(\alpha)$. $\gamma$ is not of any importance to me.

I tried solving this system of equations with Maxima (software), but I don't get any results:

declare(l_1,real);
assume(l_1>=0);
declare(l_2,real);
assume(l_2>=0);
declare(l_3,real);
assume(l_3>=0);
declare(l_4,real);
assume(l_4>=0);
declare(A,real);
assume(A>=0, A<=%pi);
declare(B,real);
assume(B>=0);
declare(G,real);
assume(G>=0);

eq1: l_1*sin(A)=l_2*cos(G)+l_3*sin(B);
eq2: l_2*sin(G)+l_1*cos(A)=l_3*cos(B)+l_4;

solve([eq1, eq2], [B, G]);
[]

Does anybody know how to solve this, so that I end up with a function $\beta(\alpha)$? Thanks for your help!

$\endgroup$
  • $\begingroup$ It's a lot easier to work with if you use $a, b, c$ instead of $\alpha, \beta, \gamma$. (Interesting typo - I entered \aloha instead of \alpha.) $\endgroup$ – marty cohen Feb 11 '16 at 6:12
  • $\begingroup$ @user147623 converting to algebraic equations and using Groebener basis is an option, but how easy it is is to be seen. $\endgroup$ – Narasimham Jun 4 '16 at 17:27
1
$\begingroup$

Rearrange the two equations as follows:-

$$l_2\cos(\gamma)=l_1\sin(\alpha)-l_3\sin(\beta)$$ $$l_2\sin(\gamma)=l_3\cos(\beta)-l_1\cos(\alpha)+l_4$$

Square both sides and add the two equations to eliminate the $\gamma$ term (using the identity that $\sin^2\theta+\cos^2\theta=1$) :- $$l_2^2(\cos^2(\gamma)+\sin^2(\gamma))=l_2^2\\=l_1^2+l_3^2-2l_1l_3(\cos(\alpha)\cos(\beta)+\sin(\alpha)\sin(\beta))+2l_3l_4\cos(\beta)-2l_1l_4\cos(\alpha)$$

To solve for $\beta$, let $u(\beta)=\cos(\beta)$, so that $\sqrt{1-u(\beta)^2}=\sin(\beta)$

Thus we have

$$u(\beta)(2l_3l_4-2l_1l_3\cos(\alpha))+l_1^2+l_3^2-l_2^2-2l_1l_4\cos(\alpha)=2l_1l_3\sin(\alpha)\sqrt{1-u(\beta)^2}$$

Let us denote the following $$f(\alpha)=2l_3l_4-2l_1l_3\cos(\alpha)$$ $$g(\alpha)=l_1^2+l_3^2-l_2^2-2l_1l_4\cos(\alpha)$$ $$h(\alpha)=2l_1l_3\sin(\alpha)$$ We end up with a quadratic in $u(\beta)$ $$u(\beta)f(\alpha)+g(\alpha)=h(\alpha)\sqrt{1-u(\beta)^2}\\\Rightarrow u(\beta)^2(f(\alpha)^2+h(\alpha)^2)+u(\beta)(2f(\alpha)g(\alpha))+g(\alpha)^2-h(\alpha)^2=0\\\Rightarrow u(\beta)=\frac{-2f(\alpha)g(\alpha)\pm\sqrt{f(\alpha)^2g(\alpha)^2-(f(\alpha)^2+h(\alpha)^2)(g(\alpha)^2-h(\alpha)^2)}}{f(\alpha)^2+h(\alpha)^2}$$

Culminating in $\beta$ being $$\beta=\arccos\left[\frac{-2f(\alpha)g(\alpha)\pm\sqrt{f(\alpha)^2g(\alpha)^2-(f(\alpha)^2+h(\alpha)^2)(g(\alpha)^2-h(\alpha)^2)}}{f(\alpha)^2+h(\alpha)^2}\right]$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.